Assessment on Compensation and Job Performance of Instructors in a Higher Education Institution in Quezon City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Compensation plays a significant role in employee satisfaction in the current corporate environment. When employees go to work, it is the main reason they work hard and accomplish well. That prompted the researchers to conduct this study on the assessment of compensation and job performance of instructors in a higher education institution. It aims to identify how the institution compensates employees despite the no-tuition-fee program. It also aims to assess its influence on the instructor's job performance, compensation, and motivation. The researchers used a correlational-quantitative research design as a basis for how the entire research study was conducted. The study's respondents are instructors of the subject higher education institution in Quezon City. The researchers used a random sampling technique to gather information. This sampling technique seeks an unbiased selection of respondents. This is because every individual will have the same probability of being chosen as a respondent. The research instrument is a self-created questionnaire reviewed by a research teacher, adviser, and statistician. The findings of the respondents' survey questionnaire were used to produce primary and secondary data. Data collected from the survey was categorized, statistically analyzed, and tabulated. The Likert Scale used has ranged from Strongly Agree to Disagree Strongly. This lets the survey developer gain a clear overview of people's opinions. Based on the study's findings, there is no significant relationship between compensation in terms of duties and responsibilities, bonuses, and honorarium and level of performance in terms of workload, productivity, and work environment. This study revealed the relationship between compensation and job performance in the subject company. Thus, the following recommendations are hereby presented: the instructors should participate more in training, seminars, and webinars to develop their knowledge, especially the 24- to 27-year olds; among the variables of assessment on compensation, honorarium has the lowest results; strengthen the honorarium, the institution should fairly compensate when it comes to extra effort of employees and also as a modest gesture of appreciation and; on the three variables of the level of instructor's performance, the workload has the lowest level of performance. Higher education institutions should improve workload management to ensure the welfare of the instructors. It can boost instructors' total productivity and ensure their work is of the highest quality.
Keywords: assessment; compensation; job performance; instructors; higher education institution